Practical engineering management of offshore oil and gas platforms - Samie, Naeim Nouri (Cambridge, MA : Gulf Professional Publishing is an imprint of Elsevier, 2016)
"Practical Engineering Management of Offshore Oil and Gas Platforms" delivers the first must-have content to the multiple engineering managers and clients devoted to the design, equipment, and operations of offshore oil and gas platforms.Concepts explaining how to interact with the various task forces, getting through bid proposals, and how to maintain project control are all covered in the necessary training reference. Relevant equipment and rule of thumb techniques to calculate critical features on the design of the platform are also covered, including tank capacities and motor power, along with how to consistently change water, oil, and gas production profiles over the course of a project.The book helps offshore oil and gas operators and engineers gain practical understanding of the multiple disciplines involved in offshore oil and gas projects using experience-based approaches and lessons learned.Delivers the first ever must-have content to the multiple engineering managers and clients devoted to the design, equipment, and operations of offshore oil and gas platforms Contains rules of thumb techniques to calculate critical features on the design of the platformIncludes practical checklists for project estimates and cost evaluation for effective project execution in budgeting and schedulingHelps offshore oil and gas operators and engineers gain practical understanding of the multiple disciplines involved in offshore oil and gas projects using experience-based approaches and lessons learned
Pt. 2. Management, Budgeting and Scheduling of Offshore Platforms Design -- BALANCING BETWEEN CLIENT AND TASK FORCE ENGINEERS: Client requests -- Engineering team requirements -- Disciplines/engineers mobilization and requests -- HANDLING DESIGN DOCUMENTATION: Master document register -- Interdisciplinary checks/discipline interfaces -- Document control center -- Vendor data controller -- Engineering disciplines tasks -- General items to be checked in quotation -- Planning and project control department -- PROPOSAL PREPARATION: Familiarizing with project requirements -- Cost order of magnitude and approximate cost -- Proposal preparation organization -- Man-hour weight distribution -- Unit cost calculation -- Miscellaneous costs -- Changes/variation orders -- PLANNING THE PROJECT BUDGET: Budget proposal -- Project costs and planning -- Expected income and deficits -- Expected deviations -- Proposals and incentives.
Includes bibliographical references (pages 523-524) and index.
Keywords: Drilling platforms; Drilling platforms